Fertility of undiluted ram epididymal spermatozoa stored for several days at 4°C - D. Fernández Abella; M. Da Costa; Y. Guérin; J.L. Dacheux (Animal, 2015)
In vitro preservation of the male gamete is a challenge in the development of artificial insemination techniques for domestic animals. Specific strategies and diluents have been developed for the preservation of the fertilizing ability of the semen for each species. However, the epididymal medium has been demonstrated to be the best sperm environment to maintain sperm viability over several days and weeks for mammals. The aims of this study were to evaluate the motility and in vivo fertility of ram epididymal spermatozoa when the semen was stored for up to 4 days at 4°C undiluted in epididymal plasma. The study was undertaken with two ovine breeds (Ile de France and Corriedale). The motility of epididymal spermatozoa was better preserved in the undiluted epididymal fluid than when epididymal spermatozoa were diluted in classic ovine extender such as skim milk. During storage, the decrease in the percentage of motile sperm was lower if the epididymal spermatozoa were collected immediately after epididymal sampling than 24 h after castration or animal death. The fertility obtained after cryopreservation of the stored sperm and subsequent intrauterine insemination ranged from 55% to 24% following 24 to 96-h sperm storage. There was a linear regression relationship between fertility and the number of motile sperm inseminated for both breeds. These results show that it is possible to keep epididymal sperm motile and fertile for several days without dilution. Such a method of sperm preservation could be a final possibility for animals of high genetic value or for endangered species when the collection of semen before death of the animal is not possible.